2018
DOI: 10.4315/0362-028x.jfp-17-507
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Several Antimicrobials Used in a Postchill Decontamination Tank against Salmonella and Campylobacter on Broiler Carcass Parts

Abstract: New microbial performance standards for chicken parts necessitate postchill antimicrobial interventions to make poultry parts safer for consumers. This research was conducted to determine the effectiveness of antimicrobials (0.003% chlorine; 0.07% acidified sodium chlorite [ASC], 0.07 or 0.1% peracetic acid [PAA], and 0.35 or 0.60% cetylpyridinium chloride [CPC]) when used in a postchill decontamination tank to reduce Salmonella and Campylobacter on broiler chicken parts (including breasts, thighs, wings, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 20 publications
4
33
0
Order By: Relevance
“…In two studies from Nagel et al [14] and Park et al [27] higher concentrations of 1000 and 1200 ppm PAA were used as dip treatments, which led to reductions of 2.0 log 10 cfu/ml and 2.6 log 10 cfu/g skin, respectively. Zhang et al [28] used concentrations of 700 and 1000 ppm PAA in a postchill decontamination tank, both concentrations achieved a reduction of 1.5 log 10 cfu/ml on chicken parts. A lower concentration of 200 ppm PAA as spray treatment had no significant effect on Campylobacter counts in another study [29].…”
Section: Resultsmentioning
confidence: 99%
“…In two studies from Nagel et al [14] and Park et al [27] higher concentrations of 1000 and 1200 ppm PAA were used as dip treatments, which led to reductions of 2.0 log 10 cfu/ml and 2.6 log 10 cfu/g skin, respectively. Zhang et al [28] used concentrations of 700 and 1000 ppm PAA in a postchill decontamination tank, both concentrations achieved a reduction of 1.5 log 10 cfu/ml on chicken parts. A lower concentration of 200 ppm PAA as spray treatment had no significant effect on Campylobacter counts in another study [29].…”
Section: Resultsmentioning
confidence: 99%
“…However, antimicrobial interventions such as postchill immersion tanks or spraying systems that use a higher concentration of antimicrobials with short contact times have been proven to be an added hurdle after primary chilling which further facilitates the reduction of pathogens on poultry carcasses ( Nagel et al., 2013 ). In addition to the antimicrobial interventions for the chicken carcasses, cutup parts are also now being subjected to antimicrobial treatment in the postcutup decontamination tank to provide added antimicrobial efficacy against Salmonella and Campylobacter in the processing plants ( Zhang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…can significantly lower the risk of human campylobacteriosis. Internationally, various bactericidal chemicals have been tested as processing aids with the aim of reducing pathogenic bacteria on processed poultry carcasses [19,22,23]. In this study, four sanitizers were tested at different temperatures (22 °C = ambient temperature, 15 °C = prechilling, 4 °C = chilling) relevant to Australian poultry meat processing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported minimal effects of ASC in reducing the level of Salmonella and Campylobacter spp. [22]. In the present study, ASC was acidified using citric acid.…”
Section: Discussionmentioning
confidence: 99%